PELATIHAN MEDIA PEBELAJARAN FELIZ DALAM MENINGKATKAN KEMAMPUAN LITERASI DIGITAL MAHASISWA UNIVERSITAS ASAHAN - Hanina; Heni Subagiharti; Diah Syafitri Handayani; Anita Purba; Tuti Herawati (Smart Education, 2026)
This community service program aimed to improve the digital literacy skills of Universitas Asahan students through the use of Feliz as an interactive learning media. The activity responded to students’ difficulties in evaluating digital information, using digital tools, understanding digital ethics, and creating digital content. The program used a training method supported by material presentation, media demonstration, direct practice, mentoring, and evaluation. The participants were 50 students of the Faculty of Teacher Training and Education, Universitas Asahan. Data were collected through observation, pretest, and posttest, then analyzed using descriptive quantitative analysis. The results showed an increase in all dimensions of digital literacy. Information evaluation increased by 33.5%, digital tools usage increased by 36%, digital ethics and security increased by 51%, and content creation increased by 67%. The average student understanding also increased from 51.5% to 85%. These results indicate that Feliz effectively supports interactive, practical, and engaging learning. Therefore, Feliz can be used as a digital learning media to strengthen students’ digital literacy in higher education.